The distribution of Meiofauna community related to salinity gradient in the Ham Luong estuary, Mekong river - Sinh, Nguyen Van; Kim Phuong, Nguyen Thi; Quang, Ngo Xuan (Academia Journal of Biology, 2013)
Seventeen taxa of meiofauna community in the Ham Luong estuary were investigated and comprised. Free-living nematodes  were the most dominant and diverse group, presenting about 77% in the total of meiofauna density. Meiofauna density varied from 135.7 ± 33.5 inds/10 cm² to 1782.0 ± 199.5 inds/10 cm². The meiofauna density shows a decreasing trend from inland station to the brackish water station and it is increasing at mouth station. Significant differences in meiofauna density, diversity and Hill’s indices were found between stations. The ANOSIM showed significant differences between stations in meiofauna composition (overall R = 0.972, p = 0.1%). The SIMPER analysis clarifies that the average similarity within stations was quite high, changing from EHL3 (76.2%) to EHL1 (86.1%).